Atomic hydrogenation-induced paramagnetic-ferromagnetic transition in zinc ferrite. Issue 15 (15th November 2016) - Xiang, Qing-Yun; Wu, Dan; Bai, Yang; Yan, Kai; Yao, Wen-Qing; Zhang, Li; Zhang, Jing; Cao, Jiang-Li
Abstract: A paramagnetic-ferromagnetic transition was observed in normal spinel zinc ferrite (ZnFe2 O4 ) during atomic hydrogenation at room temperature. Magnetic measurements showed enhanced ferromagnetic property with increasing hydrogenation time. The hydrogenated ZnFe2 O4 has normal spinel structure according to X-ray diffraction (XRD) and Raman analyses. Iron hydride was found from the XRD and X-ray absorption fine structure results. No A–B site ions exchange was observed in the x-ray absorption spectra while the atomic distances of Fe–O, Zn–O, Fe–Fe, Zn–Zn and Fe–Zn coordinations were reduced. A hybrid of Fe 2+ and Fe 3+ in hydrogenated ZnFe2 O4 can be further revealed through deconvolution of x-ray absorption near edge structure. The paramagnetic-ferromagnetic transition and enhanced ferromagnetic property were mainly due to the formation of iron hydride and the B-site super-exchange interactions of Fe 2+ and Fe 3+ .